Relevance of The Gift of The Magi with Gift-Giving Trend in Society - Ariq Galuh Anggoro; Muhyiddin Fajar Nugroho Gunawan; Muhamad Romdoni (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
The purpose of this study was to identify and analyze gift-giving aspects using an situational irony that contains inside the O. Henry’s short story “The Gift of The Magi”. This qualitative study is used to provide a deeper analysis of how the gift-giving trend is society by identify the main story, analyze the gift-giving aspects, create and conduct an small online survey to local society and at the end giving the results of the surveys. This to tells the other people how the gift-giving trend in today’s society looked like now just like on the story.